Synthesis and optoelectronic properties of quaternary GaInAsSb alloy nanosheets. (17th November 2016) - Chen, Xinliang; Li, Honglai; Qi, Zhaoyang; Yang, Tiefeng; Yang, Yankun; Hu, Xuelu; Zhang, Xuehong; Zhu, Xiaoli; Zhuang, Xiujuan; Hu, Wei; Pan, Anlian
Abstract: Quasi-one-dimensional (1D) nanostructures have been extensively explored for electronic and optoelectronic devices on account of their unique morphologies and versatile physical properties. Here, we report the successful synthesis of GaInAsSb alloy nanosheets by a simple chemical vapor deposition method. The grown GaInAsSb alloy nanosheets are pure zinc-blende single crystals, which show nanosize-induced extraordinary optoelectronic properties as compared with bulk materials. μ -Raman spectra exhibit a multi-mode phonon vibration behavior with clear frequency shifts under varied laser power. Photoluminescence measurements reveal a strong light emission in the near-infrared region (1985 nm), and the obtained Varshni thermal coefficients α and β are smaller than those of the bulk counterparts due to the size confinement effect. In addition, photodetectors (PDs) based on these single-alloy nanosheets were constructed for the first time. The PDs show a strong response in the near-infrared region with the external quantum efficiency of 8.05 × 10 4 %, and the responsivity of 0.675 × 10 3 A W −1 . These novel nanostructures would make contributions to the study of fundamental physical phenomena in quasi-1D nanomaterial systems and can be potential building blocks for optoelectronic and quantum devices.